Association of ACE gene A2350G and I/D polymorphisms with essential hypertension in the northernmost province of China. (2nd January 2018) - Sun, Feifei; He, Ning; Zhang, Keyong; Wu, Nan; Zhao, Jingbo; Qiu, Changchun
ABSTRACT: Angiotensin converting enzyme (ACE) gene, as a strong candidate gene for essential hypertension(EH), has been extensively studied. In this study, we carried out a population-based case-control study to explore whether ACE gene I/D and A2350G polymorphisms could consider to be risk factors for EH. A total of 2040 subjeces were recruited from Chinese Han in this study, out of which 1010 were cases and 1030 were normotensive individuals. ACE gene A2350G and I/D polymorphisms were amplified by polymerase chain reaction (PCR) and A2350G polymorphism was detected after restriction enzyme digestion with BstuI. Besides, we choosed 10% samples randomly sequencing to verify the accuracy of results. Genotype and allele frequencies distribution of I/D and A2350G in EH and control groups were significantly different. After grouped by sex or age, there were still statistical significances for two polymorphisms. In dominant and recessive model of A2350G, we found significant differences between two groups, respectively. For ACE I/D polymorphism, we observed that the existence of dramatical difference in dominant model between two groups, while in recessive model, marginally significant difference was found. Among the four haplotypes composed by ACE gene A2350G and I/D, haplotype G-D reached the statistical significance in two groups, and exhibited to be a risk factor for the development of EH, whose P < 0.001 and OR 95%CI = 1.639(1.435–1.872), while the other haplotypes were the protective factors and decreased the susceptibility to EH(P < 0.05). ACE gene A2350G and I/D polymorphisms were associated with increasing the risk of suffering from EH in the northernmost province of China individuals, with D allele and G allele individuals had a higher risk of EH(OR = 1.443, 95%CI = 1.273–1.636 and OR = 1.481, 95%CI = 1.303–1.684).